Synthesis Of Garlic Compound Vinyl-Dithiin And Its Derivatives, And Their Anti-Fungal Determination Using Bioautography Methode - C Hanny Wijaya (Jurnal Teknologi dan Industri Pangan, 2000)
Improvement on stability, physical characteristics and physiological activities of vinyl-dithiin has been attempted through oxidation and methylation. A bioautography method with Cladosporium cucumerinum showed that the presence of sulphoxide compound increased the anti-fungal activity sharply. Best activity was obtained with the compounds with SSO functional group. Activity was slightly decreased by addition of methyl-group. Stereoisomer also influenced the activity of compound, although not to significantly. Isomer of 3,4-dihidro-3-isopropenil-5-metil-4H-1, 2-ditiin-1-oxide has interesting properties such as crystallized easily, posses weak odor and relatively strong in anti fungal activity. A Simple methallylsynthesis procedure for disufide has been developed using metallyl chloride as starting material.